2019
DOI: 10.2478/remav-2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

House Price Convergence on the Primary and Secondary Markets: Evidence from Polish Provincial Capitals

Abstract: The aim of this study is to identify whether there is a common house price trend across provincial capitals in Poland. The log t regression is the main method of analysis. Additionally, traditional convergence tests based on the concepts of β- and σ-convergence are used. The obtained results indicate that the cities do not share a common price in the long-run. There are, however, convergence clubs on both primary and secondary markets. In each club, house prices across cities tend to converge to their own stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
4
15
1
Order By: Relevance
“…Summarising the overall convergence analysis, it should be stressed that all research methods used in this study rejected the possibility of its occurrence across the Polish residential rental markets, which is in line with other analyses studying convergence or differentiation in the Polish real estate market; see, for example, Żelazowski ( 2019 ), Gnat ( 2016 ), Dittmann ( 2014 ), Wiśniewski and Brzezicka ( 2020 ), Tomal ( 2019a ), Tomal and Gumieniak ( 2020 ).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Summarising the overall convergence analysis, it should be stressed that all research methods used in this study rejected the possibility of its occurrence across the Polish residential rental markets, which is in line with other analyses studying convergence or differentiation in the Polish real estate market; see, for example, Żelazowski ( 2019 ), Gnat ( 2016 ), Dittmann ( 2014 ), Wiśniewski and Brzezicka ( 2020 ), Tomal ( 2019a ), Tomal and Gumieniak ( 2020 ).…”
Section: Resultssupporting
confidence: 83%
“…
Fig. 6 Spatial distribution of convergence clubs: in the Polish rental housing market identified based on the trend component of time series extracted using a the Hodrick–Prescott filter, b the boosted Hodrick–Prescott filter, c the Butterworth filter and d the Christiano–Fitzgerald filter; e in the Polish sales secondary housing market according to estimates by Tomal ( 2019a , b )
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have in turn shown that in the fifteen Polish urban markets there are three groups of cities distinguished by the convergence of residential prices on the primary market that tend to approach the respective common price levels in these groups, but are not geographically distributed (Matysiak & Olszewski, 2019). Similar conclusions, though referring to both the primary and secondary markets, have also been drawn from other independent studies (Tomal, 2019). Some similarities and convergence in housing prices can also be observed between voivodeships; however, studies using this approach do not give unambiguous results and should be interpreted with caution (Żelazowski, 2019).…”
Section: Literature Reviewsupporting
confidence: 65%